Nanostructuring Ferroelectrics via Focused Ion Beam Methodologies. (10th October 2016) - Burns, Stuart R.; Gregg, J. Marty; Nagarajan, Valanoor
Abstract : As we reach the physical limit of Moore's law and silicon based electronics, alternative schemes for memory and sensor devices are being proposed on a regular basis. The properties of ferroelectric materials on the nanoscale are key to developing device applications of this intriguing material class, and nanostructuring has been readily pursued in recent times. Focused ion beam (FIB) microscopy is one of the most significant techniques for achieving this. When applied in tandem with the imaging and nanoscale manipulation afforded by proximal scanning force microscopy tools, FIB‐driven nanoscale characterization has demonstrated the power and ability which simply may not be possible by other fabrication techniques in the search for innovative and novel ferroic phenomena. At the same time the process is not without pitfalls; it is time‐consuming and success is not always guaranteed thus often being the bane in progress. This balanced review explores a brief history of the relationship between the FIB and ferroelectrics, the fascinating properties it has unveiled, the challenges associated with FIB that have led to alternative nanostructuring techniques and finally new ideas that should be explored using this exciting technique. Abstract : Recently, the use of focused ion beam microscopy to nanostructure ferroelectric and multiferroic materials has unveiled some interesting new physics despite the initial problems faced with this fabrication technique. The basic principles, history, pitfalls and future promise of nanostructuring ferroic materials with focused ion beams are explored.